Feminicídio como discurso: feminismo e antifeminismo - Agnoletto, Jéssica Cristina Trevisan (2020)
This research aims to analyze the functioning of the feminicide discursive object in feminist and anti-feminist controversial discourses related to the Feminicide Law. For this purpose, cuttings and analyzes are made of thirteen articles in the legal area, published between 2015 and 2018, approaching the theme of femicide and the law related to it. Thus, the research seeks to describe how the images of women are (re)formulated in these discourses, in addition to analyzing how they articulate knowledge and powers over women and the feminine, in relation to feminist and antifeminist discourses, and in favor or against the law of femicide. In the first chapter, we produced our theoretical-methodological framework from the writings of Michel Foucault (1979; 2015; 2017) about how discursive objects are (re)formulated and constructed their meanings, and Eni Orlandi's writing (1996) to define the controversial discursive typology. In the second chapter, we present the most relevant historical aspects, focused on meetings, conferences and official documents produced around violence against women, outlining a path that culminated in the creation of the popular Feminicide Law. In the third chapter, we discuss the main theories around the different feminist and anti-feminist movements, as well as list the points in common between the different feminist approaches and anti-feminist currents, having as theoretical basis the writings of Margaret McLaren (2016), Camille Paglia (1992), Suzanne Venker and Phyllis Schlafly (2015) among others. In chapter four, we analyze the corpus, associating them with feminist and anti-feminist discourses related to the feminicide discursive object and the women's images (re)formulations. In addition, we exam if these discourses refute or corroborate with the new qualifier of heinous crime, promulgated by the Feminicide Law. We identified that the majority of the discourses are registered in the feminist discursive formation and, consequently, the minority of the discourses belong to the anti-feminist discursive formation. Among these discourses, we verified that most part of them formulates the image of women as victims of enderbased violence, and claims that femicide is a real problem which needs attention and intervention from both public policies and the legal system. In counterpart, there are few discourses declaring that there is no gender violence.Furthermore, feminist discourses portray the image of women as victims of such violence and that they seek equality in society, while anti-feminist discourses claim that women and men are equal and that such gender laws are seen as a privilege for women.